Net Neutrality and High Speed Broadband Networks: Evidence from OECD Countries - Wolfgang Briglauer; Carlo Cambini; Klaus Gugler; Volker Stocker (International Telecommunications Society (ITS), 2021)
Network neutrality regulations are intended to preserve the Internet as a non-discriminatory, public network and an open platform for innovation. Whereas the U.S. recently reversed its regulations, thus returning to a less strict regime, the EU has maintained its course and recently revised implementation guidelines for its strict and rather interventionist net neutrality regulations. To this day, there exist only a few U.S.-focused empirical investigations on the impact of network neutrality regulations, based on rather broad measures of investment activities. Our paper provides the first estimation results on the causal impact of net neutrality regulations on new high-speed (fiber-optic cable-based) infrastructure investment by Internet service providers (ISPs) and on related consumer subscription to fiber-based broadband connection services. We use a comprehensive OECD panel data set for 32 countries for the period from 2003 to 2019 and various panel estimation techniques, including instrumental variables estimation. Our empirical analysis is based on theoretical underpinnings derived from a simplified model in a two-sided market framework. Based on our theoretical analysis, we derive testable propositions for monopolistic and duopolistic ISPs. We find empirical evidence that net neutrality regulations exert a direct negative impact on fiber investments and an indirect negative impact on fiber subscriptions. Our results, which are in line with our theoretical propositions, strongly suggest that policymakers should refrain from imposing strict net neutrality regulations.
Keywords: L52; L96; L98; 330; Net neutrality; high-speed broadband; investment; consumer subscriptions; OECD panel data